2021
DOI: 10.1002/aenm.202101050
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Dissolution of Pt‐Based Electrocatalysts through the Electronic Metal–Support Interaction

Abstract: Suppressing the Pt dissolution still remains a big challenge in improving the long‐term stability of Pt‐based catalysts in electrochemical energy conversion. In this work, the degradation of Pt nanoparticles is successfully suppressed via weakening the Pt–O dipole effect by adjusting the electronic structure of surface Pt atoms. The specially designed graphitic‐N‐doped carbon nanosheets with balanced N content and graphitization degree as well as fewer defects are prepared for anchoring Pt nanoparticles to enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 35 publications
1
65
0
Order By: Relevance
“…2h), which indicated the weaker dipole effect between the Fe centers and chemisorbed oxygen in Fe-SA/BNC. 43,44 This result further established that B-doping could optimize the desorption of the oxygen intermediates during the ORR process by modulating the electronic configuration of adjacent Fe–N 4 sites.…”
Section: Resultsmentioning
confidence: 71%
“…2h), which indicated the weaker dipole effect between the Fe centers and chemisorbed oxygen in Fe-SA/BNC. 43,44 This result further established that B-doping could optimize the desorption of the oxygen intermediates during the ORR process by modulating the electronic configuration of adjacent Fe–N 4 sites.…”
Section: Resultsmentioning
confidence: 71%
“…A higher sp 2 carbon content and fewer structural defects (lower I D / I G ratio) of GD materials could provide for different MSI that favors better ECSA CO as well as MA retention after the ADT. Although the exact correlation of MSI and its effect on the durability of the PEMFC catalysts is not yet well understood and defined, the results within this study suggest that this parameter could play an important role in understanding the origin of better catalyst durability and should therefore be further addressed in upcoming studies. , …”
Section: Resultsmentioning
confidence: 89%
“…Although the exact correlation of MSI and its effect on the durability of the PEMFC catalysts is not yet well understood and defined, the results within this study suggest that this parameter could play an important role in understanding the origin of better catalyst durability and should therefore be further addressed in upcoming studies. 41 , 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also evaluated the dissolution of Pt NPs by analyzing the Pt species dissolved in electrolytes after 20k cycles by ICP‐MS, which showed that the dissolved Pt content for Pt‐700 catalysts was substantially lower than that for Pt/C (0.232 ng vs 40 ng). [ 49 ] The Pt particles from the Pt/C catalyst are ≈1.7× smaller than those from the Pt‐700 catalyst (≈3 nm vs 5 nm), and it is well known that smaller Pt particles are more prone to dissolution than larger ones. [ 50–52 ] However, the antidissolution improvement of ≈170× far exceeds what would be expected based purely on differences in the particle size, and suggests that a further electronic effect may be largely responsible for the difference in Pt dissolution.…”
Section: Resultsmentioning
confidence: 99%